Design and Construction of a Beam Balance. - Duhimbazimana, Brian (Kabale University, 2025)
The main aim of this project is to design and construct a beam balance from locally available materials which is used to measure unknown masses by comparing their weight to a known standard weight. The project aims to create a precision balance that can accurately measure weight of various objects from smaller objects to larger items of about 5 kilograms. The methodology employed in the project typically involves selecting appropriate materials (piece of timber) for the balance s beam, as well as designing a steady and stable base to support the balance. The construction process involves assembling the components and calibrating the balance to ensure accurate readings.